2010
DOI: 10.1007/s00264-010-1102-9
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of opening wedge high tibial osteotomy augmented with a Biosorb® wedge and fixed with a plate and screws in 124 patients with a mean of ten years follow-up

Abstract: The objective of this work was firstly to evaluate the long-term results of medial opening wedge high tibial osteotomy (HTO) and secondly to evaluate the tolerance and integration of a Biosorb® wedge (β Tricalcium Phosphate, SBM Company, Lourdes, France). The series consisted of 124 knees in 110 patients, 74 men and 36 women, with mean age of 53.23±10.68 years (range 32-74) and treated between June 1995 and November 2000 for medial compartment knee osteoarthritis by the senior author. The mean preoperative Lys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
51
1
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 79 publications
(59 citation statements)
references
References 27 publications
3
51
1
4
Order By: Relevance
“…Finally, despite our trust in opening wedge osteotomies [24], we think that, at the femoral level, one should perform a closing wedge osteotomy to avoid excessive lengthening of the limb (double opening).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Finally, despite our trust in opening wedge osteotomies [24], we think that, at the femoral level, one should perform a closing wedge osteotomy to avoid excessive lengthening of the limb (double opening).…”
Section: Discussionmentioning
confidence: 96%
“…It is well indicated for "young" and active people (less than 65 years of age) with moderate arthrosis (narrowing joint line up to 100% without any bone wear or instability). Nevertheless, it is a demanding surgery with the risk of excessive over or under correction which can quickly lead to failure [8,24,26] or an oblique joint line leading to more difficulties in performing TKR (Fig. 1).…”
Section: Introductionmentioning
confidence: 99%
“…Retrospective studies of opening-wedge osteotomy have shown survival rates (rates of procedures not converted to total knee arthroplasty) ranging from 51% to 97.6% after ten years of follow-up [4][5][6][7][8][9][10][11][12][13][14][15][16] . However, there is a lack of radiographic and clinical long-term results from well-designed prospective studies.…”
mentioning
confidence: 99%
“…At final follow-up 88% classified themselves as satisfied or very satisfied with their outcome (Saragaglia 2011). Two Japanese studies have shown superior survival rates at long term follow up; the exact role of cultural and ethnic factors in these studies is unclear, the results in this population nonetheless, speak for themselves. The first study used HTLCWOs stabilized using a Giebel plate, aiming for 10 degrees of anatomic valgus or placement of the mechanical axis within the centre of the lateral compartment, in 118 knees in patients of mean age 62.9 years, whose mean flexion contracture was 7.7 degrees, with mean follow-up of 14.4 years.…”
Section: Wwwintechopencommentioning
confidence: 80%